2002
DOI: 10.1046/j.1471-4159.2002.01106.x
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of nitric oxide‐cyclic GMP signalling in CNS cells and itspossible regulation by cyclic GMP

Abstract: Physiologically, nitric oxide (NO) signal transduction occurs through soluble guanylyl cyclase (sGC), which catalyses cyclic GMP (cGMP) formation. Knowledge of the kinetics of NO-evoked cGMP signals is therefore critical for understanding how NO signals are decoded. Studies on cerebellar astrocytes showed that sGC undergoes a desensitizing profile of activity, which, in league with phosphodiesterases (PDEs), was hypothesized to diversify cGMP responses in different cells. The hypothesis was tested by examining… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
36
0
2

Year Published

2004
2004
2017
2017

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 46 publications
4
36
0
2
Order By: Relevance
“…The mechanism responsible for GC desensitization is unknown and is currently under investigation. Previously, circumstantial evidence indicated that it was related to the level of cGMP (13), and all of the data in the present study (with and without PDE inhibition) would be consistent with this proposal.…”
Section: Differential Potency Of No For Gc-coupled Receptors In Cellssupporting
confidence: 92%
See 4 more Smart Citations
“…The mechanism responsible for GC desensitization is unknown and is currently under investigation. Previously, circumstantial evidence indicated that it was related to the level of cGMP (13), and all of the data in the present study (with and without PDE inhibition) would be consistent with this proposal.…”
Section: Differential Potency Of No For Gc-coupled Receptors In Cellssupporting
confidence: 92%
“…GC and PDE Activities with Partial PDE Inhibition-Cells such as striatal neurons (13) and aortic smooth muscle (14) exposed to high NO concentrations produce a cGMP response having a triphasic shape resembling that found in platelets exposed to a low sildenafil concentration (1 M) (Fig. 3a).…”
Section: Expression Of Gc-coupled No Receptor Subunit Mrna Inmentioning
confidence: 91%
See 3 more Smart Citations